Status of Natural Terrestrial Vegetation in Gujarat - a Reassessment - Dixit, A. M.; Geevan, C. P.; Silori, C. S. (Indian Forester, 2001)
The paper examines the trends in the status of natural terrestrial vegetation in Gujarat under three major categories viz. forests, scrubs and grasslands. Information on various aspects of types, extent and changes in the above categories were collected from three major sources including the published and unpublished reports of Gujarat State Forest Department, biennial reports of Forest Survey of India and vegetation map of French Institute of Pondicherry. Satellite remote sensing data is also used to assess the vegetation quality using commonly used vegetation index i.e. Normalized Difference Vegetation Index (NDVI). The actual forest cover is 66.66% of that reported and therefore the forest cover of the State after applying corrections will be about 6.4% of total geographical area. The study recorded a decline of about 5,800 km2 area under dense category in last three decades. Adequacy of reporting categories in discerning trends in vegetal cover of Gujarat and the disparities between administrative data on forest and land-use on one hand and the FSI assessment on the other have been examined. Digital imagery analysis has been undertaken, in an illustrative sense, to show that, without too much effort, it is possible to significantly improve the understanding of vegetation status. This exercise clearly shows that improvements in the Forest Survey of India assessments will considerably help in monitoring the forest cover changes and help in identifying vegetal cover changes in arid and semi-arid regions. Based on the available data on Gujarat and its limitations, we have contemplated certain possibilities for improving the data inventory to facilitate meaningful ecological monitoring.